2017
DOI: 10.5897/ajar2016.11922
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and abundance of emerging invasive weeds in central Western part of Ethiopia

Abstract: Invasive alien weed species; are non-indigenous species that have adverse economic, environment and ecological effects on habitats where they have been introduced, either accidentally or deliberately, outside their normal past or present distribution. The objective of this study was to determine the distribution and abundance of emerging invasive weeds in West Shewa and East Wollega Zones of Western Oromia. The biophysical survey was conducted by stopping along main and sub-roads accessible for, vehicle at 8 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
4
3
0
Order By: Relevance
“…as among the most occurring alien invasive species in many habitats of eastern and southern African countries. Furthermore, our current invasion distribution model result is in parallel with studies conducted in different parts of Africa (Dlamini 2016;Fessehaie and Tessema 2014;Fufa et al 2017;Jaca and Condy 2017;Nel et al 2004). Like the study by Bellard et al (2018) proves that climate change has affected the distribution of invasive species causing expansions in climatically suitable habitats worldwide, this research evinces that future climate change would cause a similar increase of invasion in the climatically suitable areas of S. didymobotrya in Africa.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…as among the most occurring alien invasive species in many habitats of eastern and southern African countries. Furthermore, our current invasion distribution model result is in parallel with studies conducted in different parts of Africa (Dlamini 2016;Fessehaie and Tessema 2014;Fufa et al 2017;Jaca and Condy 2017;Nel et al 2004). Like the study by Bellard et al (2018) proves that climate change has affected the distribution of invasive species causing expansions in climatically suitable habitats worldwide, this research evinces that future climate change would cause a similar increase of invasion in the climatically suitable areas of S. didymobotrya in Africa.…”
Section: Discussionsupporting
confidence: 85%
“…It can easily establish itself in diverse habitat types, including grasslands, woodlands, forests, riparian zones, dumpsite, disturbed area, and coastal scrub (Tamiru 2017;Witt and Luke 2017). For instance, high invasion of S. didymobotrya was reported in forest reserves in Uganda (Winterbottom and Eilu 2006), in degraded land, urbanized land, coastline, savanna, and grassland of southern Africa (Nel et al 2004;Rambuda and Johnson 2004;Terzano et al 2018) and in several parts of Ethiopia (Fessehaie and Tessema 2014;Fufa et al 2017;Shiferaw et al 2018;Tamiru 2017). Its further expansion would worsen the problem, leading to great environmental and socio-economic damage.…”
Section: Introductionmentioning
confidence: 99%
“…(2010) [18] have also observed Parthenium infestations along road sides, habitation areas such as towns, waterways and crop lands. Similar findings were reported elsewhere in different parts of the country ( [5,1,18,28] . Our results are also in line with Mcconnachie et al (2011) [22] who reported the suitability of disturbed habitats such as roadsides, railway tracks, building areas and agricultural areas for Parthenium establishment because of lack of competition.…”
Section: Respondents Socio-demographic Statussupporting
confidence: 92%
“…Taye et al, (2010) have also observed Parthenium infestations along road sides, habitation areas such as towns, waterways and crop lands. Similar findings were reported elsewhere in different parts of the country (Berhanu et al 2015;Jemal and Taye 2015;Amare et al 2017;Reda and Tewelde, 2018).…”
Section: Reported Thatsupporting
confidence: 91%